Major discrepancy between clinical diagnosis of death and anatomopathological findings in adolescents with chronic diseases during 18-years - Ribeiro, Maira P.; Duarte-Neto, Amaro N.; Dolhnikoff, Marisa; Lindoso, Livia; Lourenço, Benito; Marques, Heloisa H.; Pereira, Maria F.B.; Cristofani, Lilian M.; Odone-Filho, Vicente; Campos, Lucia M.A.; Sallum, Adriana M.E.; Carneiro-Sampaio, Magda; et al. (Clinics, 2023)
Objectives: To evaluate the inconsistency between clinical diagnosis of death and autopsy findings in adolescents with chronic diseases. Methods: A cross-sectional study including a sample of adolescents’ autopsies who died in a pediatric and adolescent tertiary hospital over 18 consecutive years. During this period, there were n = 2912 deaths, and n = 581/2912(20%) occurred in adolescents. Of these, n = 85/581(15%) underwent autopsies and were analyzed. Further results were divided into two groups: Goldman classes I or II (high disagreement between main clinical diagnosis of death and anatomopathological findings, n = 26) and Goldman classes III, IV or V (low or no disagreement between these two parameters, n = 59). Results: Median age at death (13.5 [10‒19] vs. 13 [10‒19] years, p = 0.495) and disease duration (22 [0‒164] vs. 20 [0‒200] months, p = 0.931), and frequencies for males (58% vs. 44%, p = 0.247) were similar between class I/II vs. class III/IV/V. The frequency of pneumonia (73% vs. 48%, p = 0.029), pulmonary abscess (12% vs. 0%, p = 0.026), as well as isolation of yeast (27% vs. 5%, p = 0.008), and virus (15% vs. 2%, p = 0.029) identified in the autopsy, were significantly higher in adolescents with Goldman class I/II compared to those with Goldman class III/IV/V. In contrast, cerebral edema was significantly lower in adolescents of the first group (4% vs. 25%, p = 0.018). Conclusion: This study showed that 30% of the adolescents with chronic diseases had major discrepancies between clinical diagnosis of death and autopsy findings. Pneumonia, pulmonary abscess, as well as isolation of yeast and virus were more frequently identified at autopsy findings in the groups with major discrepancies.